MinT-trial: Mindfulness versus cognitive behavioural therapy in Tinnitus patients: protocol for a randomised controlled, non-inferiority trial - Rademaker, Maaike Maartje (BMJ Open, 2020)
INTRODUCTION: Chronic subjective tinnitus is a condition that affects 5.1% to 42.7% of the population, depending on the definition and studied population. Evidence-based treatment options are limited. Cognitive Behavioural Therapy (CBT) has been proven effective to improve quality of life and to diminish tinnitus distress. Positive short-term effects of mindfulness-based interventions on tinnitus distress have been reported; however, the longer term effects remain to be studied. METHODS AND ANALYSIS: We designed a monocentre randomised controlled, non-inferiority trial to compare the effectiveness of mindfulness-based cognitive therapy (MBCT) and CBT in chronic tinnitus patients. Fifty-four patients (≥32 on the Tinnitus Functional Index (TFI), suffering from tinnitus for at least 6 months) will be included in the trial and randomised into one of two intervention groups. One group will receive MBCT, the other group will receive CBT. Our primary objective is to determine whether MBCT is non-inferior to (as good as) CBT on tinnitus distress (TFI) in chronic tinnitus patients at 12 months follow-up after end of therapy. Non-inferiority will be declared if the mean decrease in TFI score for MBCT is no worse than the mean decrease in TFI score in CBT, with statistical variability, with a margin of 13 points. Most secondary objectives (tinnitus severity of problem, tinnitus intrusiveness, quality of life, anxiety, depression, symptoms of psychopathology, perceived tinnitus complaints, coping style (mostly validated questionnaires)) are expected to show non-inferiority to MBCT compared with CBT. We expect a significant difference between MBCT and CBT for mindfulness awareness. ETHICS AND DISSEMINATION: This research protocol was approved by the Institutional Review Board of the UMC Utrecht (NL67838.041.18, V.4, April 2019). The trial results will be made accessible to the public in a peer-review journal. TRIAL REGISTRATION NUMBER: NL7745.